Determine the Mean Increase in Hemoglobin Levels From Baseline after Liposomal Iron Therapy in Anemic Patients - Hina Memon, Kanwal Ayub, Ghulam Sughra Bhellar, Haleema Shah, Wasifa Shaukat, Khadija Bano (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Encapsulation of iron in a micronized form into liposomes is a recent advancement aimed at improving iron absorption and gastrointestinal tolerance. This innovative oral iron delivery system enhances bioavailability and reduces adverse effects by minimizing direct contact between iron and the intestinal mucosa. Objectives: To determine the mean increase in hemoglobin levels from baseline after liposomal iron therapy in anemic patients. Methodology: This Quasi-experimental study was conducted at Department of Obstetrics & Gynecology, Jinnah Postgraduate Medical Centre (JPMC), Karachi from 11th August 2021 to 10th February 2022. A total of 60 anemic female patients aged 18 to 60 years were included. Patients on immunosuppressive therapy or with chronic kidney or liver disease were excluded. Baseline demographic data were recorded. Hemoglobin levels were measured at baseline and after 12 weeks of oral liposomal iron therapy. Results: The mean age of participants was 36.05 ± 11.22 years, and the majority (63.33%) were between 18 to 40 years. Mean BMI was 28.07 ± 3.31 kg/m². The mean baseline hemoglobin was 8.13 ± 0.85 g/dL, which significantly increased to 10.05 ± 1.05 g/dL after 12 weeks of liposomal iron therapy (p < 0.001), indicating a substantial improvement in anemia status among participants. Conclusion: Liposomal iron therapy resulted in a significant mean increase in hemoglobin levels in anemic patients over 12 weeks, suggesting that it is an effective and well-tolerated treatment option. Keywords: Anemia, liposomal iron, hemoglobin levels, oral iron therapy, micronized iron.